Diversity of genotypes and pathogenicity of H9N2 avian influenza virus derived from wild bird and domestic poultry - Yang, Qinhong; Ji, Jia; Yang, Jia; Zhang, Yongxian; Yin, Hongbin; Dai, Hongyang; Wang, Wei; Li, Suhua (Frontiers in Microbiology, 2024)
Abstract：The H9N2 subtype is a predominant avian influenza virus (AIV) circulating in Chinese poultry, and has forming various genotypes (A-W) based on gene segment origins. This study isolated eleven H9N2 strains from fecal samples of overwintering wild birds and their proximate domestic poultry in Yunnan Provence, China, including four from common cranes (Grus grus), two from bar-headed geese (Anser indicus), and five from domestic poultry (Gallus gallus). Phylogenetic analysis revealed that the five isolates from domestic birds and one from a bar-headed goose belong to genotype S, while the remaining five isolates from wild birds belong to genotype A. These birdderived strains possess deletions in the stalk domain of NA protein and the N 166 D mutation of HA protein, typical of poultry strains. When representative strains of the two genotypes were inoculated into Yunnan mallard ducks, a local breed sharing water resources with wild birds, genotype S H9N2 demonstrated oropharyngeal shedding, while genotype A H9N2 exhibited cloacal shedding and high viral loads in the duodenum. Both strains caused significant pathological injuries, with genotype S inducing more severe damage to the thymus and spleen, while genotype A caused duodenal muscle layer rupture. These findings suggest that at least two genotypes of H9N2 are currently circulating in Yunnan, and the Yunnan mallard ducks potentially act as an intermediary in the interspecies transmission. These insights highlight the analysis of the current epidemiological transmission characteristics of H9N2 among wild and domestic birds in China.